Strategic human resource management : a guide to action - Armstrong, Michael (Kogan Page, 2015)
Provides practical guidance on implementing the complex HR strategies that have been formulated by many practitioners, academics and consultants. This book contains chapters on HRM, HR strategy, the formulation and implementation of strategy, roles in strategic HRM, and strategic reward.